Marine-Derived Bioactive Compounds: A Promising Strategy for Ameliorating Skeletal Muscle Dysfunction in COPD - Meiling Jiang; Peijun Li; Xiaoyu Han; Linhong Jiang; Lihua Han; Qinglan He; Chen Yang; Zhichao Sun; Yingqi Wang; Yuanyuan Cao; Xiaodan Liu; Weibing Wu (Marine Drugs)
Chronic obstructive pulmonary disease (COPD) is frequently accompanied by skeletal muscle dysfunction, a critical and severe extrapulmonary complication. This dysfunction contributes to reduced exercise capacity, increased frequency of acute exacerbations, and elevated mortality, serving as an independent risk factor for poor prognosis in COPD patients. Owing to the unique physicochemical conditions of the marine environment, marine-derived bioactive compounds exhibit potent anti-inflammatory and antioxidant properties, demonstrating therapeutic potential for ameliorating COPD skeletal muscle dysfunction. This review summarizes marine-derived bioactive compounds with promising efficacy against skeletal muscle dysfunction in COPD, including polysaccharides, lipids, polyphenols, peptides, and carotenoids. The discussed compounds have shown bioactivities in promoting skeletal muscle health and suppressing muscle atrophy, thereby providing potential strategies for the prevention and treatment of COPD skeletal muscle dysfunction. These findings may expand the therapeutic strategies for managing COPD skeletal muscle dysfunction.